Impact of glucan type exopolysaccharide (EPS) production on technological characteristics of sourdough bread - Ispirli, Humeyra; Ozmen, Duygu; Yilmaz, Mustafa Tahsin; Sagdic, Osman; Dertli, Enes (ELSEVIER SCI LTD, 2020)
In this study, technological role of a-glucan with (alpha 1-3) and (alpha 1-6) glycosidic linkages produced by Lactobacillus reuteri E81 on sourdough rheology and bread texture was investigated. To achieve this, a glucan deficient Delta gtfA mutant was produced by the deletion of the glucansucrase gene from strain E81. By comparison of glucan-positive and glucan-negative strains for rheological properties of sourdough revealed that in situ a-glucan production resulted in higher elasticity in sourdough. However, no additional effect of in situ glucan on textural characteristics of bread was observed although addition of glucan ex situ at 0.09% level significantly decreased bread hardness. Scanning Electron Microscopy (SEM) images of lyophilized sourdoughs confirmed association of glucan and starch granules forming a film like structure in sourdough.
Keywords: Sourdough; Glucan; Glucansucrase; Sourdough rheology; Bread texture; LACTIC-ACID BACTERIA; WHEAT SOURDOUGH; LACTOBACILLUS; QUALITY; BAKING; Food Science & Technology